2016
DOI: 10.1002/tcr.201500256
|View full text |Cite
|
Sign up to set email alerts
|

Tetrel Bonding Interactions

Abstract: Tetrel (Tr) bonding is first placed into perspective as a σ-hole bonding interaction with atoms of the Tr family. An sp(3) R4Tr unit has four σ-holes with which a Lewis base can form a complex. We then highlight some inspiring crystal structures where Tr bonding is obvious, followed by an account of our own work. We have shown that Tr bonding is ubiquitous in the solid state and we have highlighted that Tr bonding with carbon is possible when C is placed in the appropriate chemical context. We hope that this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
151
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(163 citation statements)
references
References 99 publications
1
151
0
Order By: Relevance
“…Closely related to these interactions are those in which the bridging atom comes from the tetrel family (C, Si, Ge, etc). [16][17][18][19][20][21] There is a rapidly growing literature [22][23][24][25][26][27] that has provided a wealth of insights into the chemical and physical phenomena that underlie tetrel bonds. This larger number of substituents obstructs a clear passage of an approaching nucleophile toward the tetrel atom, [8] which can inhibit the formation of such a bond or at the least require a good deal of deformation so as to clear a space for the Lewis base.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Closely related to these interactions are those in which the bridging atom comes from the tetrel family (C, Si, Ge, etc). [16][17][18][19][20][21] There is a rapidly growing literature [22][23][24][25][26][27] that has provided a wealth of insights into the chemical and physical phenomena that underlie tetrel bonds. This larger number of substituents obstructs a clear passage of an approaching nucleophile toward the tetrel atom, [8] which can inhibit the formation of such a bond or at the least require a good deal of deformation so as to clear a space for the Lewis base.…”
Section: Introductionmentioning
confidence: 99%
“…But the question arises as to whether a tetrel atom, within a tetravalent covalent bonding situation, is limited to only a single such bond. [25,[55][56][57][58][59][60] There has been a certain amount of consideration of the general topic of hypervalent pnicogen, halogen, and even aerogen atoms [9,[61][62][63][64][65][66][67][68][69][70][71][72][73][74] but not in the context of tetrel atoms, which have their own unique electronic and spatial issues. The theoretical literature to date has little to say on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…electron acceptor) has been explored by Mani and Arunan [41]. They demonstrated that the carbon atom in fact could act as an electrophilic center which can non-covalently bond with electron-rich entities leading to noncovalent carbon bonding, following a nomenclature analogous to other σ-hole interactions [7][8][9][10][11][12][13][14][15][16][17]. The theoretical predictions were confirmed experimentally by Guru Row's group [42], thus validating the existence of this type of bonding by means of X-ray charge density analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the correct description and understanding of noncovalent interactions between molecules is essential for being successful in this field of research. In general, strong and highly directional interactions, such as hydrogen bonding and σ-hole bonding [7][8][9][10][11][12][13][14][15][16][17], and less directional forces like ion pairing are used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,11,12,13,14 Over the past few years other non-conventional noncovalent interactions have gained attention, such as tetrel bonding, 15,16,17,18,19 pnictogen bonding, 20,21,22,23,24,25,26,27,28,29,30,31 chalcogenide bonding, 32,33,34,35,36,37,38,39,40,41,42,43,44 and even aerogen bonding. 45 All follow the same bonding scheme, namely a -hole, 46 which can be viewed comparably to hydrogen bonding: X-D … A, where X is any atom, D is the donor atom and A is the acceptor atom.…”
Section: Introductionmentioning
confidence: 99%